Does Mixed-Ownership Reform Catalyzes High-Quality Enterprise Development? Evidence from China - Ruonan Fang; Jingxia Yu (Journal of Frontier in Economic and Management Research, 2025)
The high-quality development of a nation's economy fundamentally relies on the high-quality development of every micro-enterprise. As a critical institutional innovation in China's economic system, clarifying the relationship between mixed-ownership reform and corporate high-quality development is essential. This study empirically examines the impact ofmixed-ownership reform on enterprise high-quality development using 2013–2023 Chinese A-share listed companies as the sample. Research findings demonstrate that mixed-ownership reform promotes enterprise high-quality development, while ownership concentration exerts an inhibitory effect. Further analysis reveals that the marginal benefits of mixed-ownership reform on enterprise high-quality development are stronger in private-owned enterprises; Mixed-ownership reform improves corporate performance by inhibiting corporate financialization. These discoveries provide valuable insights for deepening the understanding of mixed-ownership reform.